Assessment of factors related to treatment failure and recurrence of superficial dermatophytosis - Ibrahim, Evana; Mowla, Rafiqul; Faroque, Abu S. M. O.; Shahrin, Sabrina; Kulsum, Umme (International Journal of Research in Medical Sciences, 2024)
Background: Superficial dermatophytosis, commonly known as ringworm, is a fungal infection of the skin, hair, or nails caused by dermatophytes, primarily belonging to the genera Trichophyton, Microsporum, and Epidermophyton. Despite being a superficial infection, the rising incidence of treatment failure and recurrence has become a matter of concern in recent years. Methods: This prospective observational study, conducted at the department of dermatology and venereology of Chittagong Medical College Hospital, aimed to investigate the epidemiological factors associated with treatment failure and recurrent cases of superficial dermatophytosis. The study spanned from March 2022 to February 2023, involving 249 participants diagnosed with Tinea corporis, Tinea cruris, Tinea facies, or Tinea pedis. Factors such as excessive sweating, use of warm water, clothing habits, sharing practices, and topical corticosteroid application were analyzed. Results: The most common age group affected was 21-30 years, with a male preponderance (1.6:1). Excessive sweating, wearing water-soaked garments, and sharing towels were prevalent among participants. After 4 weeks of treatment, 81.5% achieved complete cure, but 52.7% of these cases experienced a recurrence within the subsequent 4 weeks. Multivariate analysis identified sharing towels, family history of dermatophytosis, and past topical steroid use as significant risk factors for treatment failure/recurrence. Conclusions: The study emphasizes the importance of linen (sharing towels) in the transmission of dermatophytosis and highlights the increased risk associated with a family history of the condition. Additionally, the injudicious use of topical steroids emerged as a significant factor contributing to treatment failure and recurrence.